Regional GDP in the UK, 1861-1911: new estimates - Geary, Frank; Stark, Tom (The Economic history review, 2015)
This article compares the Geary-Stark method for distributing known GDP totals across regions with a variation suggested by Crafts. Tests of the Geary-Stark method confirm that it generates accurate estimates of regional GDP. There are practical and conceptual problems with Crafts' extension, and it is not tested nor is it testable. New estimates of regional GDP for the period 1861 to 1911 contradict Crafts's suggestion of rising regional inequality. Purchasing power parity adjustments do not alter this trend. The new estimates confirm Ireland's post-Famine catch-up. The great bulk of Irish labour productivity growth can be accounted for by an upward shifting production function, though it can be argued that that portion of growth that represents catch-up may be attributable to labour force decline.